2015
DOI: 10.1088/1748-0221/10/05/t05002
|View full text |Cite
|
Sign up to set email alerts
|

Visible spectroscopy calibration transfer model in determining pH of Sala mangoes

Abstract: The purpose of this study is to compare the efficiency of calibration transfer procedures between three spectrometers involving two Ocean Optics Inc. spectrometers, namely, QE65000 and Jaz, and also, ASD FieldSpec 3 in measuring the pH of Sala mango by visible reflectance spectroscopy. This study evaluates the ability of these spectrometers in measuring the pH of Sala mango by applying similar calibration algorithms through direct calibration transfer. This visible reflectance spectroscopy technique defines a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Yahaya et al (2015) found that the spectral model established by the QE65000 spectrometer could be transferred to the FieldSpec 3 spectrometer more easily and in a better way than another portable spectrometer, suggesting that the two spectrometers could be replaced by each other [ 27 ]. In this study, QEPro and FieldSpec 4 were the upgraded spectrometers of QE65000 and FieldSpec 3, respectively, suggesting that QEPro and FieldSpec 4 also could replace each other.…”
Section: Discussionmentioning
confidence: 99%
“…Yahaya et al (2015) found that the spectral model established by the QE65000 spectrometer could be transferred to the FieldSpec 3 spectrometer more easily and in a better way than another portable spectrometer, suggesting that the two spectrometers could be replaced by each other [ 27 ]. In this study, QEPro and FieldSpec 4 were the upgraded spectrometers of QE65000 and FieldSpec 3, respectively, suggesting that QEPro and FieldSpec 4 also could replace each other.…”
Section: Discussionmentioning
confidence: 99%
“…The coefficient of determination, R 2 and root mean square error (RMSE) will represent the accuracy of the generated linear line while its slope will represent the influence of UVA-LED wavelength in defining the discoloration magnitude or sensitivity of the film. R 2 and RMSE is a widely recognized statistical tool in representing the accuracy of the measurement technique (Yahaya et al, 2015;Zhao & Wu, 2018 ; Sun, Li & Niu, 2018): Area under the curve5…”
Section: Methodsmentioning
confidence: 99%
“…Currently, studies are concentrated on the similar questions for the same samples derived from different instruments, measurement conditions, or other aspects (called calibration transfer) [15][16][17][18][19]. Many algorithms have successfully resolved these calibration transfer, such as direct standardization (DS) [20,21], piecewise direct standardization (PDS) [22,23], orthogonal signal method (OSC) [24,25], wavelet transform (WT) algorithm [26,27], and canonical correlation analysis(CCA) [28,29].…”
Section: Introductionmentioning
confidence: 99%